The digital transformation roadmap in Erasmus mobility application procedures: Transforming paper-based workflows into web-based integrated applications - Cardoso, Abílio (2019)
In the process of organising exchange mobility, students and higher education staff members must conclude trilateral Learning Agreements (LA) that are the basis for the recognition of academic qualifications obtained abroad. While LA documents may be considered essential to an adequate organisation of credit mobility, there are several issues that hamper their preparation. In fact, the interlocutors involved are often not clearly defined, the information needed to build the agreements is rarely available online and in up to 75% of the cases, students need to change their learning agreements after their arrival at the receiving Higher Education Institutions (HEI). Furthermore, as the process is mainly paper-based, it is error prone and time consuming. This paper describes the ongoing project developed by the authors aiming to develop a web-based software platform to automate the process of submitting applications for UPT students exchange and UPT academic and non-academic staff exchange (STA and STT) within the Erasmus+ programme. The project addresses the dematerialization of the process of organising exchange mobility, transferring a paper-based workflow, which is reliant on timely postal deliveries for signature purposes, into an online system that will allow students and staff to gain considerable time when preparing their studies or work abroad and induce a greater degree of flexibility and efficiency when needing to revise the LA.